THE ROLE OF ACTIVE GAMES IN EDUCATION OF PRESCHOOL CHILDREN: THE ROLE OF ACTIVE GAMES IN EDUCATION OF PRESCHOOL CHILDREN - ismatov, abduqodir (Физическое воспитание, спорт и здоровье, 2022)
The article discusses the possibilities for children to find active ways to solve a game problem, creating opportunities for their game.